Multipurpose jacket with thermal technology (Blueprint) / Anis Fathiah Fazer ... [et al.]. - Fazer, Anis Fathiah; Wahir, Izzah Amirah; Mohd Sabri, Nur Najihah; Suhaimi, Nur Elia Farhana; Ramli, Elly Elyanna; Mohd Zaid, Ummi Liyana; Raja Fuad, Raja Noor Shareena (2024)
The multipurpose jacket with thermal technology is a ground-breaking innovation in outerwear, flawlessly combining modern technology and versatile design. The jacket has integrated thermal technology that delivers customizable warmth while adjusting to changing weather conditions. The jacket is designed for motorcycle riders and individuals who have experienced chilly weather. The use of cutting-edge materials provides maximum insulation while remaining lightweight and breathable. The jacket appeals to a wide range of activities, from outdoor experiences to urban commuting, providing customers with a versatile solution for different climates. These versatile jackets feature a sleek and contemporary design that prioritizes usefulness without sacrificing style. The thermal technology incorporated strategically throughout the garment enables users to easily manage their body temperature, resulting in a comfortable and adaptive outerwear experience. Whether battling chilly winds or unexpected temperature variations, these jackets redefine adaptability, thus becoming a must-have wardrobe staple for individuals seeking a perfect balance of design and performance.